Analyzing Students' Dubbing Performance Quality on SEA Subtitling and Dubbing Project in English Department of Universitas Negeri Padang - Aqilah, Putri Ashma; Hilmi, Lafziatul (Universitas Negeri Padang, 2024)
The purpose of this research is to analyze the quality of student dubbing projects in the SEA subtitling-dubbing class, as well as to see how dubbing activities impact the motivation of students to learn English. This research employed descriptive and quantitative methods. The researcher used a transcription table to collect data, which included documentation of students' dubbing project results in the SEA subtitling-dubbing course in the form of a table, and also used a questionnaire with ten statements about students' motivation through dubbing activities. The participants were 20 students who took the SEA subtitle-dubbing class period from January to June 2023. According to research findings, the quality of student dubbing performance in the SEA class is fairly good. Furthermore, based on the questionnaire completed by the students, the researcher discovered that the students' motivation to carry out this dubbing project was quite high, with the students feeling enthusiastic about learning English through several steps of dubbing processes that they had completed.